Factor each problem completely. Solve for x: X^2 – 12 = -4x. Please show the steps on how you got your answer. Thanks!

x^2 – 12 = -4x x^2 -12 + 4x = 0 x^2 + 6x -2x -12 = 0 ( x + 6) ( x - 2) = 0

Question

Asked 12/17/2010 4:32:02 AM

Updated 9/15/2014 12:40:02 AM

1 Answer/Comment

Rating

0

x^2 – 12 = -4x

x^2 -12 + 4x = 0

x^2 + 6x -2x -12 = 0

( x + 6) ( x - 2) = 0

x^2 -12 + 4x = 0

x^2 + 6x -2x -12 = 0

( x + 6) ( x - 2) = 0

Added 9/15/2014 12:40:02 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [9/15/2014 1:05:23 AM]

Working with polynomials: (2x4 + 3)(4x³+ 2) **Weegy:** (2x4 + 3)(4x³+ 2) = 8x^12 + 4x^4 + 12x^3 + 6
(More)

Question

Expert Answered

Updated 7/16/2014 11:07:55 AM

1 Answer/Comment

(2x^4 + 3)(4x^3 + 2) = 8x^7 + 4x^4 + 12x^3 + 6

Added 7/16/2014 11:07:54 AM

This answer has been confirmed as correct and helpful.

Working with polynomial: (12y³ + 8 y² + 20y) / 2y **Weegy:** x+2y+z --> x = -2y-z (More)

Question

Expert Answered

Updated 7/16/2014 11:09:47 AM

1 Answer/Comment

(12y³ + 8y² + 20y) / (2y)

= (12y³/2y) + (8y²/2y) + (20y/2y)

= 6y^2 + 4y + 10

= (12y³/2y) + (8y²/2y) + (20y/2y)

= 6y^2 + 4y + 10

Added 7/16/2014 11:09:46 AM

This answer has been confirmed as correct and helpful.

Working with polynomial: (5x – 3.6) – (4x + 1.2)

Question

Expert Answered

Updated 7/3/2014 1:57:21 PM

1 Answer/Comment

Working with polynomial: (3x^2 + 3x) + (4x + 4). Please show the steps on how you got your answer. Thanks!

Question

Not Answered

Updated 8/10/2014 5:55:48 PM

1 Answer/Comment

(3x^2 + 3x) + (4x + 4)

= 3x^2 + 3x + 4x + 4;

= 3x^2 + 7x + 4

= 3x^2 + 3x + 4x + 4;

= 3x^2 + 7x + 4

Added 8/10/2014 5:55:48 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/10/2014 5:57:18 PM]

Working with polynomial: (6x^2 - 25x - 10) / (3x + 2)

Question

Not Answered

Updated 7/27/2014 12:19:20 PM

1 Answer/Comment

(6x^2 - 25x - 10) / (3x + 2)

= (6x^2/3x+2) - (25x/3x+2) - (10/3x+2)

= 2x - 29/3 R. 28/3

= (6x^2/3x+2) - (25x/3x+2) - (10/3x+2)

= 2x - 29/3 R. 28/3

Added 7/27/2014 12:19:20 PM

This answer has been confirmed as correct and helpful.

27,178,522

questions answered

There are no comments.